PENGARUH EARNING MANAGEMENT DAN CORPORATE SOSIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN MEKANISME GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Arhdum, Zioldy; Taufik, Taufeni; Ratnawati, Vince (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2017)
This study was conducted to examine the effect of earnings management andcorporate social responsibillity on company value. In this study, the researcher alsoincorporated the mechanism of good corporate governance as a moderationvariable that tested the two independent variables against company value. Theresearch method used is descriptive method verifikatif by using tool of moderateregression analysis test. For the purpose of the study, data collection was conductedusing the Companys top 50 issuers with the highest corporate governance (CG)score of 2014 based on the assessment of the Indonesian Institute for CorporateDirectorship (IICD) using the ASEAN Corporate governance guidelines. The result ofthis research shows that earnings management influence to corporate value,corporate social responsibility influence to company value, and good corporategovernance mechanism that is managerial ownership, institutional ownership andindependent commissioner managed moderate earnings management relationshipand corporate social responsibility to company value.